MgAl-CO3 layered double hydroxide as potential filler in substrate layer of composite membrane for enhanced carbon dioxide separation. Issue 5 (October 2021) - Fajrina, N.; Yusof, N.; Ismail, A.F.; Jaafar, J.; Aziz, F.; Salleh, W.N.W.; Nordin, N.A.H.M.
Abstract: The harvest of biogas resources is a promising means of delaying fossil-fuel depletion and simultaneously tackling climate change. Membrane technology is a promising method for an economic upgrade of biogas with the benefits of low energy consumption and environmentally friendliness, leading to intensive research in the fabrication of high-separation CO2 membranes. In this study, a substrate of composite membrane for CO2 /CH4 separation was developed by incorporating MgAl-CO3 layered double hydroxides (LDH) synthesized via a simple co-precipitation method into polysulfone (PSf) polymer. The fabricated substrate hybrid LDH/PSf membrane was coated with a low-cost industrial PEBAX-polymer for minimizing surface defects as well as act as selective layer to form composite membrane for gas permeance. The physicochemical changes were analyzed by using XRD, FTIR, TGA, SEM, contact angle, AFM and tensile test. The impact of LDH loading (1, 3 and 5 wt%) in the substrate layer and operating pressure (1, 3 and 5 bar) on the composite membrane were thoroughly investigated. The composite membrane has increased the CO2 permeance by 55–113% as compared to pristine PSf membrane. Particularly, the composite membrane with 3.0 wt% LDH in the substrate layer has displayed the highest CO2 /CH4 selectivity of 38.5. The distinct advantages in terms of facile fabrication with the right loading confer the LDH as potential filler in substrate layer of composite membrane with great potential for large-scale CO2 capture and separation. Graphical Abstract: ga1 Highlights: MgAl-CO3 LDH was synthesis by co-precipitate method. LDH was incorporated into PSf substrate layer for CO2 separation from CH4 . The composite membrane with 3.0 wt% LDH in the substrate layer showed the best separation performance. LDH in substrate layer was capable in increasing the hydrophilic substrate layer.